2012
DOI: 10.5941/myco.2012.40.1.027
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Synergistic Effects of Silver Nanoparticles Synthesized Using Soil Fungi of High Altitudes of Eastern Himalaya

Abstract: Fifty three fungi isolated from soils of different microhabitats of eastern Himalayan range (3,400~3,600 msl) were screened for mycosynthesis of silver nanaoparticles (AgNPs) and their efficacy as antimicrobials were assessed in combination with commonly used antibiotics. Three isolates Aspergillus terreus SP5, Paecilomyces lilacinus SF1 and Fusarium sp. MP5 identified based on morphological and 18S rRNA gene sequences were found to synthesize AgNPs. These nanoparticles were characterized by visual observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…Therefore, it can be concluded that the biosynthesized AgNPs can find applications as antibacterial agent against multi-drug resistant bacteria either singly or in combination with antibiotics. Studies have demonstrated synergistic antibacterial effects of AgNPs on some antibiotics against Gram-positive and Gram-negative bacteria (Fayaz et al 2010;Devi and Joshi 2012). Through the disruption of cell wall by some antibiotics, the AgNPs can be easily internalized by the bacterial cell thereby enhancing toxicity to the cell.…”
Section: Antimicrobial Activities Of Biosynthesized Agnpsmentioning
confidence: 99%
“…Therefore, it can be concluded that the biosynthesized AgNPs can find applications as antibacterial agent against multi-drug resistant bacteria either singly or in combination with antibiotics. Studies have demonstrated synergistic antibacterial effects of AgNPs on some antibiotics against Gram-positive and Gram-negative bacteria (Fayaz et al 2010;Devi and Joshi 2012). Through the disruption of cell wall by some antibiotics, the AgNPs can be easily internalized by the bacterial cell thereby enhancing toxicity to the cell.…”
Section: Antimicrobial Activities Of Biosynthesized Agnpsmentioning
confidence: 99%
“…These particles are well known as a potent antimicrobial against almost all bacterial strains (Ebrahiminezhad et al, 2016a;2016b;2016d). AgNPs are also effective against antibiotic resistant microorganisms and increase the efficiency of antibiotics (Devi and Joshi, 2012;Fayaz et al, 2011;Ruden et al, 2009;Shahverdi et al, 2007). In addition to antimicrobial applications, AgNPs have various other applications such as molecular labelling and detection, diagnostics, antimicrobial coating, optics, wound healing, antitumor and burn lesson protection and treatment (Sondi and Salopek-Sondi, 2004;Ansari et al, 2011;Alt et al, 2004;Lee et al, 2003;Mukherjee et al, 2008;Mohanpuria et al, 2008;Ebrahimi et al, 2016;Ebrahiminezhad et al, 2016c).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that Ag NPs have synergic activities with antibiotics such as kanamycin, ampicillin, chloramphenicol, and erythromycin against grampositive and gram-negative bacteria. The combination of Ag NP with organic antibacterial agents has effective antibacterial activity (20). In other studies, the NPs offered improved properties to essential oils; Scandorieiro et al showed oregano essential oil plus Ag NPs had synergic effect against all 3 extended spectrum beta-lactamase (ESBL)-producing E. coli and this combination had bactericidal activity (21).…”
Section: Introductionmentioning
confidence: 99%